IMPLEMENTASI ZETIZEN BAGI DAYA TARIK LITERASI MEDIA GENERASI Z - Haidir Fitra Siagian; Tri Imam Fachrurrazi (Jurnal Jurnalisa: Jurnal Jurusan Jurnalistik, 2018)
Implementation or activities undertaken by Zetizen PT. Jawa Pos Group in increasing reading interest of Z generation towards the news which is presented with intergrating Zetizen newspaper published in 38 cities of 34 provinces in Indonesia, website zetizen.com with providing news contents, quizzes, and Zetizen members, social media to encourage the increase of awareness towards Zetizen products, both traffic website and newspaper readers, last offline engagement, by always being involved and creating Zetizen events and communities. Those four elements are interconnected within increasing reading interest of Z generation. The challenges faced by Zetizen PT. Jawa Pos Group is divided into two. 1) Human Resources, including; a) diversification of spirit, lack of human resources, b) Zetizen crew must have courage, develop research and understand the condition of young people. And 2) Content, including: a) Make the Zetizen news become viral, attractive, communicative, b) lack of media distribution, c) updating timeline and interesting creative videos.